The power of six - Lore, Pittacus (Penguin Books, 2012)
I am Number Seven. And I am ready.Six of us are left. We hide, blend in, avoid one another, but our Legacies are developing. And one day soon we'll be ready to fight back. Is the appearance of Number Four the sign we've been waiting for? And what about Number Five and Six? Is the raven-haired girl from my dreams one of them? A girl with powers beyond anything I have ever imagined. A girl strong enough to bring the six of us together...I an Number Seven. And I am ready to fight.